2017
DOI: 10.1155/2017/9303276
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeine on Some Selected Biochemical Parameters Using Rat Model

Abstract: Effect of caffeine on some selected biochemical parameters using rat model was investigated. Standard methods of analysis were used for the study. A total of sixty (60) rats divided equally into five groups of which one group served as the control, and the rest as test groups were used. The test rats were placed on different concentrations of caffeine for twenty-eight (28) days. Results obtained for the selected biochemical parameters revealed that AST and ALT levels of the liver increased significantly ( < 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
2
7
0
Order By: Relevance
“…The signi cant (p<0.05) decrease in RBCs and HGB levels in group III rats when compared with the control suggest possible alterations in the balance between erythropoiesis and erythrocyte destruction as well as inhibition of hemoglobin synthesis [35].…”
Section: Discussionmentioning
confidence: 86%
“…The signi cant (p<0.05) decrease in RBCs and HGB levels in group III rats when compared with the control suggest possible alterations in the balance between erythropoiesis and erythrocyte destruction as well as inhibition of hemoglobin synthesis [35].…”
Section: Discussionmentioning
confidence: 86%
“…This is not in line with the earlier observations made by Duru et al [28], on rats given "udu, an antimalarial concoction made from combination of herbal leaves, and Mbongue et al [53] on rats treated with P. guineese for 55days. Zhou et al [54] attributed body weight increase in rats to androgenic property of the substance given to the rats as a result of anabolic activity, while Agomuo et al [36]; and Yehya (2001) noted that loss in weight could be as result of increase in sympathetic tone.…”
Section: Discussionmentioning
confidence: 99%
“…Record has it that man for long has taken advantage of the therapeutic value of medicinal plant constituents on production of drugs that are effective against infectious microorganisms and disease conditions. De Silva [34]; Oladunmoye [35]; and Agomuo et al [36] reported that plant based compounds are in use of many modern medical systems.…”
Section: Introductionmentioning
confidence: 99%
“…Such an exclusion of foods from the regular diet for any reason could affect laboratory test results unless compensated for with pills or fortified food. As a third example, alcohol [7], smoking [8] and high consumption of caffeine [9] can also impact laboratory test results. Although alcohol consumption is prohibited in Saudi Arabia, its effects on different body organs can be assessed by several biochemical and hematological tests [7].…”
Section: Introductionmentioning
confidence: 99%